Growth Characteristics of Chilli Pepper (Capsicum annuum) under the Effect of Magnetizing Water with Neodymium Magnets (NdFeB) - Etimad Alattar; Khitam Elwasife; Eqbal Radwan (AGRIVITA, Journal of Agricultural Science, 2021)
The present study aims to identify the impact of magnetized water on the growth characteristics of chilli pepper (Capsicum annuum) plants. A total of 80 chilli seeds were separated into four groups: the first group was watered with non-magnetized water, while the three groups were dampened with water magnetized using 3, 6, and 9 neodymium magnets (NdFeB), respectively. The findings revealed that magnetized water caused changes in the study parameters. Although the plants watered with magnetized water were taller than the plants watered with non-magnetized water, there were no significant differences between the four groups (p = 0.224). The results revealed that the stem thickness of chilli peppers is pretty affected by the magnetized water. There was no significant difference between the four treatments (p = 0.218). The current study found that the number of leaves is significantly influenced by watering with magnetized water (p = 0.015). The leaves of chilli peppers dampened with water treated with six magnets (74.50 ± 13.57) were the highest, and those saturated with non-magnetized were the lowest in number (60.00 ± 6.09) among four groups. The influence of magnetized water relies on the number of magnets utilized for magnetizing water.